Creative capital of Siberian cities - Vavilina, Nadezhda; Parshukova, Galina; Parshukova, Polina (project baikal, 2021)
The article considers sociological theoretical approaches to the understanding of creative capital as a resource for the development of urban economies. It features methodological approaches to sociological research. The data of comparative analysis of the creative capital of Krasnoyarsk and Novosibirsk are presented. The comparative analysis was carried out on the materials of real sociological research conducted in 2020 according to a common methodology for determining a quota sample. The study was carried out on the basis of a quota sample of the city population aged 18 and over. The reliability of the data obtained was ± 3,5 %. The authors make a conclusion that there are differences in the nature of creative capital in Krasnoyarsk and Novosibirsk. This fact should condition different strategies for the development of creative industries for these cities.